Construction of hierarchical ZSM-5 zeolites by chelating-alkaline medium. (September 2021) - Yang, K.; Yan, S.; Sang, Y.; Liu, J.; Yu, L.; Yang, X.; Huang, S.
Abstract: Chelating agent, including NaF, Na4 EDTA, etc., has been introduced into the alkaline treatment of ZSM-5 zeolite. Compared with the general aqueous alkaline solution, all of the resulting chelating-alkaline media give similar alterations to the porosities. Regardless of the relative accessibility of chelating agent to the zeolite micropores, the maximum distribution of mesopore obviously shifts to the smaller dimension. Such shift in mesopore distribution is associated with the equilibrium between surface/interface etching and shielding, which is inherently directed by the transition of framework Al species. The spontaneous interplays between framework Al species and alkaline solution are altered due to the concurrent presence of chelating agent. It has been proved that the chelating agent join the transition by a joint complexation with OH − anions and the released aluminum cations. The resulting ternary intermediates ([Al(OH)n Lm ] y− ) are proposed to be responsible for the alterations to the porosities due to their expanded shielding scope on the etched surface/interface. The corresponding steric or charge effect from chelating agent has been ascertained by the designed comparative treatment experiments. The used methodology and the related fundamental understandings may enrich the tailoring tool boxes for the hierarchical zeolites. Graphical abstract: Image 1